Ecomorphology of the pectoral girdle in anurans (Amphibia, Anura): Shape diversity and biomechanical considerations. Issue 20 (17th September 2020) - Engelkes, Karolin; Kath, Lena; Kleinteich, Thomas; Hammel, Jörg U.; Beerlink, André; Haas, Alexander
Abstract: Frogs and toads (Lissamphibia: Anura) show a diversity of locomotor modes that allow them to inhabit a wide range of habitats. The different locomotor modes are likely to be linked to anatomical specializations of the skeleton within the typical frog Bauplan. While such anatomical adaptations of the hind limbs and the pelvic girdle are comparably well understood, the pectoral girdle received much less attention in the past. We tested for locomotor‐mode‐related shape differences in the pectoral girdle bones of 64 anuran species by means of micro‐computed‐tomography‐based geometric morphometrics. The pectoral girdles of selected species were analyzed with regard to the effects of shape differences on muscle moment arms across the shoulder joint and stress dissipation within the coracoid. Phylogenetic relationships, size, and locomotor behavior have an effect on the shape of the pectoral girdle in anurans, but there are differences in the relative impact of these factors between the bones of this skeletal unit. Remarkable shape diversity has been observed within locomotor groups indicating many‐to‐one mapping of form onto function. Significant shape differences have mainly been related to the overall pectoral girdle geometry and the shape of the coracoid. Most prominent shape differences have been found between burrowing and nonburrowing species with headfirst and backward burrowing species significantly differing from one another and from the other locomotor groups. The pectoral girdle shapes of burrowing species have generally larger moment arms for (simulated) humerus retractor muscles across the shoulder joint, which might be an adaptation to the burrowing behavior. The mechanisms of how the moment arms were enlarged differed between species and were associated with differences in the reaction of the coracoid to simulated loading by physiologically relevant forces. Abstract : The relationships between locomotor behavior, shape, and function of the anuran pectoral girdle were investigated. Adaptation to burrowing behavior was observed and could be explained by biomechanical requirements. Other locomotor groups showed minor or no shape differences; large shape diversity within those groups indicated many‐to‐one mapping of form onto function.